Towards an enhanced role for human biomonitoring in REACH regulation: Current landscape and future prospects - Susana Viegas; Tiina Santonen; Michael Bader; Nancy B. Hopf; Robert Pasanen-Kase; Kate Jones; Karen S. Galea; Steven Verpaele; Adrian Tristram; Ovnair Sepai; Natalie von Goetz; Paul T.J. Scheepers; et al. (Regulatory Toxicology and Pharmacology, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Spatial Distribution and AirQ + -Based Health Risk Analysis of Particulate Matter in Bangladesh’s Industrial Hubs - Md. Kamrul Hossain; Rubaiatul Islam Zerin; Humaira Rashid; Umma Suraiya Parvin Kakon; Mst. Sadia Siddika Trina; Laila Anjum Eva; Shahin Ali; Mohammad Omar Faruk Molla; Md. Saikoth Jahan; Md. Assraf Seddiky; Sazal Kumar; Mohd. Maniruzzaman; et al. (Water, Air, & Soil Pollution, 2026)
Rapid urbanisation and population growth in Bangladesh have intensified ambient particulate matter (PM 2.5 and PM 10 ) pollution, posing critical threats to public health. This study assessed PM concentration in three major industrial cities, Dhaka, Narayanganj, and Gazipur. PM concentrations were measured using an Air Particle Counter and an optimised air-quality sensor. PM measurements were conducted at 138 sampling points across Dhaka, Narayanganj, and Gazipur in October 2023, a climatologically stable late-autumn period, providing a reliable baseline for assessing ambient PM levels. Long-term chronic and acute diseases were quantified using the WHO AirQ + tool, including acute lower respiratory infection (ALRI) in children, chronic obstructive pulmonary disease (COPD), ischemic heart disease (IHD), stroke, and lung cancer (LC) in adults. The study revealed that the average PM 2.5 concentrations of 74.04, 56.70, and 63.99 µg/m 3 exceeded WHO standards in three cities and exceeded BD standards only in Dhaka, while PM 10 levels exceeded only WHO standards. A strong correlation was observed between PM 2.5 and PM 10 . Meteorological analysis indicated that wind speed and direction were key dispersion drivers, whereas temperature and humidity showed weak inverse exponential relationships with PM levels. Hazard Quotient (HQ) derivation revealed significant non-cancer health risks, with values exceeding unity. In contrast, PM 2.5 significantly affected ALRI mortality among children, with rates of 0.52, 0.44, and 0.49 per 100,000 in Dhaka, Narayanganj, and Gazipur, respectively. In adults, stroke was the leading PM 2.5 -related cause of death, with rates of 9.87, 9.13, and 9.63 per 100,000 in these cities. IHD deaths were also high, while LC and COPD mortality ranged from low to moderate. The study underscores the substantial public health implications of persistent PM pollution across Bangladesh’s industrial cities and reinforces the urgency of implementing coherent regulatory interventions. To strengthen the precision of exposure assessments and support more robust evidence-based policymaking, future investigations should incorporate multi-seasonal sampling, extended temporal monitoring, and broader spatial representation across diverse industrial zones.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Multisensory integration task–based age group classification in early-mid adulthood - Prerna Singh; Eva Ghanshani; Pooja Mahajan; Lalan Kumar; Tapan Kumar Gandhi (Medical & Biological Engineering & Computing, 2026)

Urbanization and seasonal effects on dairy cow diets and milk fatty acid profiles in the Indian Megacity of Bengaluru - Shahin Alam; Silpa Mullakkalparambil Velayudhan; Regina Roessler; Tong Yin; Sivashanmugam Parthipan; Anjumoni Mech; Nira Manik Soren; Pradeep Kumar Malik; Somu Bala Nageswara Rao; Raghavendra Bhatta; Sven König; Eva Schlecht (International Dairy Journal, 2025)

Evolving marine sedimentation, redox stratification, and biogeochemical cycling in mid- to low-latitudinal non-frozen waters during late Neoproterozoic global-scale climatic transitions - Arunava Sen; Soumik Mukhopadhyay; Eva E. Stüeken; Pradip Samanta; Subir Sarkar; Soumyadeep Bose; Shailesh Agarwal; Anurag Kumar (Precambrian Research, 2025)

The time for ambitious action is now: Science-based recommendations for plastic chemicals to inform an effective global plastic treaty - Susanne M. Brander; Kala Senathirajah; Marina O. Fernandez; Judith S. Weis; Eva Kumar; Annika Jahnke; Nanna B. Hartmann; Juan José Alava; Trisia Farrelly; Bethanie Carney Almroth; Ksenia J. Groh; Kristian Syberg; et al. (Science of The Total Environment, 2024)

Structural characterisation of the energy-conserving methyltransferase of a methylotrophic methanogenic archaeon - Tristan Reif-Trauttmansdorff; Eva Herdering; Tomas C. Pascoa; Erik Zimmer; Anuj Kumar; Stefan Bohn; Ruth A. Schmitz; Jan M. Schuller (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Seasonal variation in heavy metal intake and excretion by dairy cattle in an Indian megacity - Shahin Alam; Silpa Mullakkalparambil Velayudhan; Christian Adjogo Bateki; Pradeep Kumar Malik; Raghavendra Bhatta; Andreas Buerkert; Sven König; Eva Schlecht (Livestock Science, 2024)

Urbanisation threats to dairy cattle health: Insights from Greater Bengaluru, India - Md Shahin Alam; Silpa Mullakkalparambil Velayudhan; Debpriyo Kumar Dey; Chiamaka Adilieme; Pradeep Kumar Malik; Raghavendra Bhatta; Sven König; Eva Schlecht (Tropical Animal Health and Production, 2023)
Complex urbanisation dynamics, on the one hand, create a high demand for animal products, and on the other hand put enormous pressure on arable land with negative consequences for animal feed production. To explore the impact of accelerated urbanisation on dairy cattle health in urban farming systems, 151 farmers from different parts of the Greater Bengaluru metropolitan area in India were individually interviewed on aspects addressing cattle management and cattle health. In addition, 97 samples of forages from the shores of 10 different lakes, and vegetable leftovers used in cattle feeding were collected for nutritional analysis. Along with the use of cultivated forages, crop residues, and concentrate feed, 47% and 77% of the farmers occasionally or frequently used lake fodder and food leftovers, respectively. Nutritionally, lake fodder corresponded to high-quality pasture vegetation, but 43% of the samples contained toxic heavy metals such as arsenic, cadmium, chromium, and lead above official critical threshold levels. Therefore, lake fodder may affect cows’ health if consumed regularly; however, heavy metal concentrations varied between lakes ( P < 0.05), but not between fodder types ( P > 0.05). Although 60% of the interviewed farmers believed that their cows were in good health, logit model applications revealed that insufficient drinking water supply and the use of lake fodder negatively impacted cattle health ( P < 0.05). While it remains unknown if regular feeding of lake fodder results in heavy metal accumulation in animal products, farmers and farm advisors must address this and other urbanization-related challenges to protect cattle health. Graphical abstract

Interpreting biomonitoring data: Introducing the international human biomonitoring (i-HBM) working group's health-based guidance value (HB2GV) dashboard - Shoji F. Nakayama; Annie St-Amand; Tyler Pollock; Petra Apel; Yu Ait Bamai; Dana Boyd Barr; Jos Bessems; Antonia M. Calafat; Argelia Castaño; Adrian Covaci; Radu Corneliu Duca; Sarah Faure; et al. (International Journal of Hygiene and Environmental Health, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Life cycle assessment of bio-methane and biogas-based electricity production from organic waste for utilization as a vehicle fuel - Amar Mohan Shinde; Anil Kumar Dikshit; Monica Odlare; Eva Thorin; Sebastian Schwede (Clean Technologies and Environmental Policy, 2021)

Current strategies for mutation detection in phenotype-driven screens utilising next generation sequencing - Michelle M. Simon; Eva Marie Y. Moresco; Katherine R. Bull; Saumya Kumar; Ann-Marie Mallon; Bruce Beutler; Paul K. Potter (Mammalian Genome, 2015)

Photoperiod and temperature affects seasonal ovarian gene expression of p450 aromatase and gonadotropin receptors in Atlantic Salmon (Salmo salar L.) broodstock - Eva Andersson; Sampath R. Kumar; Jared Ackers; Geir Lasse Taranger; Sigurd Olav Stefansson; John M. Trant (Fish Physiology and Biochemistry, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)